2012
DOI: 10.1111/j.1442-9993.2011.02354.x
|View full text |Cite
|
Sign up to set email alerts
|

European rabbit survival and recruitment are linked to epidemiological and environmental conditions in their exotic range

Abstract: The European rabbit, Oryctolagus cuniculus, is threatened within its native range, yet it is a highly successful colonizing pest species across its worldwide introduced range, causing large economic losses and widespread environmental degradation. To date, there has been no long-term empirical evidence documenting the relative roles of climatic, epidemiological and biological factors in limiting life-history determinants of rabbit range and abundance. Using 12 years of capture-mark-recapture data from their ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 42 publications
(53 reference statements)
1
18
0
Order By: Relevance
“…Rabbits in arid Australia are managed using a “press and pulse” type framework (Bender, Case, & Gilpin, ), where rabbits are controlled using viral biocontrol agents ( press ) and episodes of warren ripping and baiting ( pulse ; Wells et al., ). Our finding that a sustained rate of rabbit removal of 40% provides the greatest benefit to small mammals has strong implications for the on‐ground management of rabbits in their invasive range because this press mortality rate corresponds closely to disease‐induced mortality rates following the long‐term establishment of rabbit haemorrhagic disease and myxomatosis in disease‐burdened rabbit populations (Fordham et al., ); the primary biocontrol agents used to manage rabbits in arid Australia. Therefore, if the goal of rabbit management in arid Australia is to provide benefits to small mammal populations (e.g., by facilitating increased population abundances), then it seems clear that the present management strategy, involving a sustained press at intermediate levels of mortality and/or time‐limited removals of higher fractions of the rabbit populations, is appropriate.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Rabbits in arid Australia are managed using a “press and pulse” type framework (Bender, Case, & Gilpin, ), where rabbits are controlled using viral biocontrol agents ( press ) and episodes of warren ripping and baiting ( pulse ; Wells et al., ). Our finding that a sustained rate of rabbit removal of 40% provides the greatest benefit to small mammals has strong implications for the on‐ground management of rabbits in their invasive range because this press mortality rate corresponds closely to disease‐induced mortality rates following the long‐term establishment of rabbit haemorrhagic disease and myxomatosis in disease‐burdened rabbit populations (Fordham et al., ); the primary biocontrol agents used to manage rabbits in arid Australia. Therefore, if the goal of rabbit management in arid Australia is to provide benefits to small mammal populations (e.g., by facilitating increased population abundances), then it seems clear that the present management strategy, involving a sustained press at intermediate levels of mortality and/or time‐limited removals of higher fractions of the rabbit populations, is appropriate.…”
Section: Discussionmentioning
confidence: 81%
“…These studies have shown the importance of considering ecological interactions when identifying “whole ecosystem” type responses to species management. For example, Pech and Hood () disentangled the likely effects of a downward pressure on rabbit abundance (caused by rabbit hemorrhagic disease, an important biocontrol for European rabbits in their invasive range; Fordham et al., ) on a mesopredator and a generic small native mammal. Choquenot and Forsyth () used a similar approach to establish the likely effects of controlling dingoes on kangaroo populations, showing the potential for cascading effects of controlling an apex predator.…”
Section: Introductionmentioning
confidence: 99%
“…With high recovery rates, in turn, we may expect reproductive effort and disease dynamics to have equally important effects on rabbit extinction. This is because in rabbits, density-dependent population regulation is expected to disproportionately affect juvenile survival [33], and seasonally coinciding density-dependent and disease-induced mortality may counterbalance each other.…”
Section: Discussionmentioning
confidence: 99%
“…We examined seasonal patterns in population counts from Turretfield, using capture-mark-recapture data [33]. We used data imputation to generate a continuous time series (weekly steps) of the minimum number of individuals known to be alive (MNA, based on all capture and carcass-recovery records) in different weeks between 1998 and 2013.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation